2004
DOI: 10.1080/08820530490519961
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography evaluation of macular edema after radial optic neurotomy in patients affected by central retinal vein occlusion

Abstract: OCT demonstrated resolution of the macular edema in all the eyes. This resolution is not always accompanied with an improvement in VA. Further studies are needed to better understand the efficacy of this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
1
7
0
1
Order By: Relevance
“…Similarly, Binder et al [60] reported that patients with nonischemic CRVO may respond more favorably than patients with ischemic CRVO after performing RON. Moreover, while improvements in visual acuity after RON have been confirmed by several other reports [61][62][63][64] , some studies found a resolution of macular edema that was not accompanied by an improvement in visual acuity in all eyes following RON [65,66] . On the other hand, some studies revealed that RON induce the development of retinochoroidal shunt vessels in 46.7-83.3% of patients and this may represent the mechanism of any beneficial effect this surgical procedure [67][68][69][70][71] .…”
supporting
confidence: 49%
“…Similarly, Binder et al [60] reported that patients with nonischemic CRVO may respond more favorably than patients with ischemic CRVO after performing RON. Moreover, while improvements in visual acuity after RON have been confirmed by several other reports [61][62][63][64] , some studies found a resolution of macular edema that was not accompanied by an improvement in visual acuity in all eyes following RON [65,66] . On the other hand, some studies revealed that RON induce the development of retinochoroidal shunt vessels in 46.7-83.3% of patients and this may represent the mechanism of any beneficial effect this surgical procedure [67][68][69][70][71] .…”
supporting
confidence: 49%
“…These authors thus proposed that eyes with ischaemic CRVO would not benefit from RON. Similarly, in a study by Patelli et al. (2004), including five eyes with CRVO, resolution of macular oedema occurred in all eyes after RON, but was not accompanied by an improvement in VA.…”
Section: Surgical Treatment Strategies For Central Retinal Vein Occlumentioning
confidence: 75%
“…However, the CRVO study only included cases with |≥ 3 months duration, whereas the investigational case series included many cases with shorter duration of CRVO (Weizer et al. 2003; Patelli et al. 2004; Martinez‐Jardon 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies found a resolution of macular edema that was not accompanied by an improvement in VA in all eyes following RON [120,121]. …”
Section: Surgical Approaches To Treating Rvomentioning
confidence: 99%